Improving time transfer performance for low earth orbit satellites - Pal Arora, Triyan; Petrunin, Ivan; Hill-Valler, Jaz; Anyaegbu, Esther (IEEE, 2024)
Low earth orbit (LEO) provides closer satellites with lower transmission losses and delays while struggling with a smaller field of view (FoV) and larger drag. The related works have been developed in the past utilising LEO satellites for positioning by relaying the signal from GNSS to the ground station. The following work addresses the timing aspect along with satellite positioning through ranging and limiting the position and velocity errors to provide control over the timing bias and drift errors. Using real-time two-line element (TLE) ephemeris data from a LEO satellite, the solution incorporates a linear Kalman filter to obtain predictions by updating the algorithm with a multilateration dataset from four known ground stations. The simulation dataset for satellite orbit propagation is used as ground truth to compare with the predictions and obtain position and velocity errors, leading to timing bias and drift. An error reduction of nearly 70 % was observed for position estimation, while an error reduction of nearly 30 % was found for the timing bias. The obtained value is within 0.5 ns of the 'LEO satellite positioning through the GNSS' technique. The proposed solution contributes to the evolving landscape of LEO navigation, improving positioning and timing measurement accuracy for satellite-based services.
Keywords: 40 Engineering; 4001 Aerospace Engineering; Multilateration; Kalman filter; low earth orbit (LEO); ephemeris; positioning; timing error